Corrosion behavior of the electrolytic ternary cobalt alloys with Mo(W) and Zr in alkaline solution - Nenastina, T. A.; Ved, M. V.; Sakhnenko, N. D.; Yermolenko, I. Yu.; Proskurina, V. A.; Volobuyev, M. M. (Інститут загальної та неорганічної хімії ім. В. І. Вернадського, 2019)
The ternary Co–Mo–W(Zr) coatings with total content of refractory metals of 30–40 wt.%, and Co–W–Zr alloys (12–26 wt.%) are deposited from pyrophosphate-citrate electrolytes in pulse regime. The composition of the coatings as well as the surface morphology depends on the current density. The X-ray diffraction patterns reflect the amorphous-and-crystalline ternary alloys structure. Phases of α-Co, Co–Mo intermetallic compounds, and traces of metallic molybdenum were detected in the Co–Mo–Zr coatings. Phase composition of Co–Mo–W deposits differs by emergence of Co₇W₆ phase and traces of metallic tungsten, and there is no metallic W in Co–W–Zr electrolytic alloys. The corrosion behavior of ternary coatings in alkaline medium studied by EIS shows that Co–Mo–Zr alloys are characterized by highest corrosion resistance among deposited coatings due to presence of metallic molybdenum and stoichiometric ZrO₂ with both high electrical resistivity and chemical stability. The coatings Co–Mo–W and Co–Mo–Zr containing phases of Mo or W are characterized by higher corrosion resistance as compared with that without metallic molybdenum and tungsten. The cyclic voltammetry data confirm stability of ternary coatings in alkaline solution under anodic polarization. Such properties as well as the developed globular surface make materials promising for use as anodes in fuel cells in particular based on alkali electrolytes.
Корозійна поведінка електролітичних потрійних сплавів кобальту з Mo(W) та Zr у лужному розчині
Keywords: electrodeposition; cobalt alloys; corrosion resistance; refractory metal